Mode of attachment and pathology caused by Parorchites Zederi in three species of penguins: Pygoscelis Papua, Pygoscelis Adeliae, and Pygoscelis Antarctica in Antarctica - Martín, María A.; Ortiz, Juana M.; Seva, Juan; Vidal, Virginia; Valera, Francisco; Benzal, Jesús; Cuervo, José J.; de la Cruz, Carlos; Belliure, Josabel; Martínez, Ana M.; Diaz, Julia Inés; Motas, Miguel; et al. (Journal of Wildlife Diseases)
We identified and compared gross and microscopic lesions associated with the cestode, Parorchites zederi, in the digestive tracts of three species of penguins (Spheniscidae): the Chinstrap (Pygoscelis antarctica), Gentoo (Pygoscelis papua), and Adélie penguins (Pygoscelis adeliae). The gastrointestinal tracts of 79 recently dead individuals (71 chicks and eight adults) were collected in locations throughout the Antarctic Peninsula during summer field trips in 2006–09. Parorchites zederi was found in the small intestine of 37 animals (47%), and 23 (62%) of these had parasite-associated lesions. The cestodes were either free in the intestinal lumen, clustered within mucosal ulcers, or deeply embedded in the intestinal wall. Histopathologic changes were most severe in adult Gentoo Penguins and included transmural fibrogranulomatous enteritis, hemorrhage, and edema. This report of pathology associated with P. zederi in the digestive tracts of penguins can serve as reference to monitor health in Antarctic birds associated with environmental changes. Fil: Martín, María A. Universidad de Murcia; España Fil: Ortiz, Juana M. Universidad de Murcia; España Fil: Seva, Juan. Universidad de Murcia; España Fil: Vidal, Virginia. Universidad de Murcia; España. Museo Nacional de Ciencias Naturales; España Fil: Valera, Francisco. Consejo Superior de Investigaciones Científicas. Estación Experimental de Zonas Aridas; España Fil: Benzal, Jesús. Consejo Superior de Investigaciones Científicas. Estación Experimental de Zonas Aridas; España Fil: Cuervo, José J. Museo Nacional de Ciencias Naturales; España Fil: de la Cruz, Carlos. Universidad de Extremadura; España Fil: Belliure, Josabel. Universidad de Alcalá; España Fil: Martínez, Ana M. Universidad Nacional Autónoma de México; México Fil: Diaz, Julia Inés. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Estudios Parasitológicos y de Vectores. Universidad Nacional de La Plata. Facultad de ...